P1237 Attitudes towards sexual counselling of patients with gynaecological malignancies – preliminary results of the survey examining ENYGO members perspective. (1st November 2019) - Kacperczyk-Bartnik, J; Nowosielski, K; Lindquist, D; Lanner, M; Nikolova, T; Vlachos, D; Selcuk, I; Pletnev, A; Zalewski, K
Abstract : Introduction/Background: Both the location of primary disease and treatment side effects may have an impact on sexual function in the population of oncogynaecological patients. Sexual health is a major compound of the quality of life, yet due to its intimate nature tends to be underserved in the routine medical care. The aim of the study was to examine prevalence, strategies, barriers and ideas for improvement of sexual counselling among specialists managing patients with gynaecological malignancies. Methodology: A self-prepared questionnaire concerning sexual counselling in gynaecological oncology practice (attitudes, behaviours, confronted difficulties and ideas for possible systemic improvements) was used in this cross-sectional study. Paper and online versions were distributed among participants of ESGO-ENYGO-ESO Masterclass. Link to the questionnaire was also shared among ENYGO members via the mailing system, ESGO social media channels, and ENYGO National Representatives. Ongoing data collection was initiated in June 2019. A total number of 99 answers from 39 countries were obtained. Results: Collecting information concerning sexual function of the majority of managed patients was reported by 36% of respondents, whereas 20% discuss the topic rarely or never. 74% stated that the subject is important or very important. However, 70% are asked by less than half of managed patients about the impact of proposed therapies on sexual function. Most frequently mentioned barriers included time deficiency (74%), insufficient specialist knowledge (53%), patient's embarrassment (46%), and lack of educational materials for patients (35%). According to respondents more widespread sexual counselling in oncological care could be achieved by preparation of educational materials for patients (80%) and healthcare providers (74%) as well as organization of workshops for professionals (64%) and patients (50%). Conclusion: The patients' needs regarding sexual counselling could be addressed better. Providing access to specialist educational programmes for both patients and healthcare providers may serve as adequate method for achieving this goal. Disclosure: Nothing to disclose.